2009
DOI: 10.1021/jp9071422
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of Water Molecules and Its Relation with the Chemistry and Physics of Liquid Water

Abstract: The literature values of the limiting ionic conductivities of H(+), OH(-), K(+), Cl(-), Ag(+), and Na(+) in water between 0 and 156 degrees C are analyzed as for the two possible mechanisms of conduction, i.e., controlled by an activation process or by the rotation of the water molecules. Plots of the data versus T(1/2) give straight lines for H(+) and OH(-), which supports the rotation control mechanism for these ions. The other ions give curved plots and therefore are investigated in terms of the activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(69 citation statements)
references
References 25 publications
10
59
0
Order By: Relevance
“…[2] Such a plot obtained for OH À was (as expected) perfectly linear and intersected the abscissa at a value corresponding to T 0 = 243.4 K or to t 0 = À29.8 8C. [2] Such a plot obtained for OH À was (as expected) perfectly linear and intersected the abscissa at a value corresponding to T 0 = 243.4 K or to t 0 = À29.8 8C.…”
Section: Direct Graphical Extrapolationmentioning
confidence: 61%
See 4 more Smart Citations
“…[2] Such a plot obtained for OH À was (as expected) perfectly linear and intersected the abscissa at a value corresponding to T 0 = 243.4 K or to t 0 = À29.8 8C. [2] Such a plot obtained for OH À was (as expected) perfectly linear and intersected the abscissa at a value corresponding to T 0 = 243.4 K or to t 0 = À29.8 8C.…”
Section: Direct Graphical Extrapolationmentioning
confidence: 61%
“…In an earlier paper intended to show the water rotation control of the conductance of OH À and H + ions directly from the linear dependence of their limiting conductivity on the square root of absolute temperature, we concluded that the conductance by OH À ions comes to a halt at 243 K. [2] Unexpectedly, it was discovered that such a halt also occurred at the same temperature for other inorganic ions; this suggested that the phenomenon is a consequence of some kind of immobilization of bulk water at that temperature. If so, it was to be expected that several more properties of water and its solutes would be affected similarly by such immobilization as a structural arrest, all of them at or near 243 K.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations